Bloody Mary. Volume 3 - Samamiya, Akaza (Shojo beat manga., 2016)
"Maria's father, Yusei, was killed by vampires- and it was Maria's own fault. Haunted by guilt, he sealed away the memory. That is, until he remembers the face of the murderous vampire ... and it looks just like Mary's! On a mission for answers, Maria comes to the kidnapped Mary's rescue, but he finds some else within Mary ..."--Cover.